Central Serous Chorioretinopathy: A Complication Associated with Behçet’s Disease Treatment - Nur Doğanay; Melike Balıkoğlu Yılmaz; Betül Orduyılmaz; Erdinç Aydın; Ali Osman Saatçi (Türk Oftalmoloji Dergisi)

(untitled)
Central serous chorioretinopathy (CSCR) is characterized by a well-defined serous choroidal detachment of the retinal pigment epithelium with one or more focal lesions of the neurosensory retina. Risk factors for CSCR are psychosocial stress, increased endogenous catecholamine, and increased endogenous cortisol. Systemic steroids can cause ocular side effects such as cataract development, increased intraocular pressure, and less frequently the development of CSCR, which can resolve spontaneously with close follow-up and simple treatment modification. CSCR should be considered in patients who complain of worsening vision under steroid treatment for pathologies requiring steroid therapy. In this study we present two patients, one man and one woman, who developed acute CSCR while under systemic steroid treatment for Behçet’s disease.